A POLITICA PARA AS MULHERES E AS MULHERES NA POLITICA COLOMBIANA - Eucaris Olaya (Universidade Federal do Maranhão, 2012)
Throughout history women have been mobilized, denounced, emancipated and claimed rights of citizenship. The achievement of these rights is one of the most important revolutions in human history. ln Colombia, women have always been present in the actions defending the ideais of independence and sovereignly ofthe territory. The search for this path of organization, aiming to elucidate the politicai theorywhich feeds the movements by women and feminists in Colombia, reveals itself as a challenge of this text, trying to understand what assumptions that contributed to the institutionalization of the discourse and the viabilily of public policies for this segment of society.